2017
DOI: 10.1016/j.cortex.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origin of nonfluency in aphasia: A path modeling approach to neuropsychology

Abstract: A major challenge in understanding the origin of clinical symptoms in neuropsychological impairments is capturing the complexity of the underlying cognitive structure. This paper presents a practical guide to path modeling, a statistical approach that is well-suited for modeling multivariate outcomes with a multi-factorial origin. We discuss a step-by-step application of such a model to the problem of nonfluency in aphasia. Individuals with aphasia are often classified into fluent and nonfluent groups for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 104 publications
(126 reference statements)
0
26
0
Order By: Relevance
“…The path models were not simply used as tools for significance testing. We applied the check procedures described in Nozari & Faroqi-Shah (2017) to first assess whether the hypothesized architecture was suitable. For example, representing inhibitory control as a single latent variable represented by scores from all the inhibitory control tests assumes that inhibitory control is a unitary construct.…”
Section: Discussionmentioning
confidence: 99%
“…The path models were not simply used as tools for significance testing. We applied the check procedures described in Nozari & Faroqi-Shah (2017) to first assess whether the hypothesized architecture was suitable. For example, representing inhibitory control as a single latent variable represented by scores from all the inhibitory control tests assumes that inhibitory control is a unitary construct.…”
Section: Discussionmentioning
confidence: 99%
“…Because the core function word measure was designed for clinical utilization, the WAB-R was used for classification of subgroups (fluent and non-fluent types of aphasia) for the main analyses, as it is one of the most popular standardized tests in clinical settings. Since it has been suggested that there is a lack of reliability in clinical judgements on fluency according to WAB-R scoring (Clough and Gordon 2020, Gordon 1998, Holland et al 1986, Nozari and Faroqi-Shah 2017, a comprehensive approach to determine subgroups of aphasia would improve our understanding of appropriateness of this measure as a clinical outcome measure. Another related limitation is that our participants with non-fluent types of aphasia fortuitously have more severe aphasia compared with their counterparts (fluent types of aphasia).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…This is potentially unsurprising as fluency as reflected here by the number of words produced per minute likely depends on multiple processes during language production including message generation, conceptual activation, grammatical encoding, phonological, articulatory and motor processes (cf. Nozari and Faroqi-Shah, 2017).…”
Section: Fluencymentioning
confidence: 99%